(untitled) (International Journal of Built Environment and Sustainability, 2021)
The COVID-19 pandemic has generated a wide range of socio-economic disruption, which causes devastating in numerous aspects. Our knowledge of the true health of the construction industry under the ravage of COVID-19 outbreak is largely based on very limited data. This study aims to assess the impact of pandemic on the construction industry through an investigation in Vietnam. Data were collected through 129 respondents whose online questionnaire survey completed according to their recent direct or indirect participation in delivering construction projects during the spread. The implications of COVID-19 on the construction industry were examined based on simple percentage analysis and Relative Importance Index approaches. Three principal facets of the construction industry were considered: firms’ business activities, project performance, and workforce demand. The findings highlighted the multilevel, multidimensional nature of the epidemic consequences on the construction sector. Notably, the revenue and profitability, in a general sense, have decreased during the COVID-19 period, while most of the production and business costs had remained unchanged. Further, the pandemic was argued to impair construction practitioners’ incomes and mental health and sabotage projects’ schedule and cost.